Advancements in antiviral approaches against foot-and-mouth disease virus: a comprehensive review - Mohamadin, Mahmoud; Manzoor, Rashid; Elolimy, Ahmed; Abdelmegeid, Mohamed; Mosad, Samah; Abd El Rahman, Sahar (Frontiers in Veterinary Science, 2025)
Foot-and-mouth disease (FMD) is a highly contagious viral disease that poses a significant threat to the global livestock industry. Despite extensive vaccination efforts, outbreaks continue to occur frequently, highlighting the need for effective therapeutic interventions. This review comprehensively examines the recent advances in antiviral therapies targeting the foot-and-mouth disease virus (FMDV), alongside an overview of recent developments in FMD vaccines. We extensively reviewed the published literature on various antiviral agents targeting FMDV, including small-molecule inhibitors, biologics, RNA-based therapeutics, gene delivery systems, and innovative approaches such as virus protease inhibitors and nanomaterials. Among the notable findings are the promising results of monoclonal antibodies, porcine interferon-α fusion proteins, and RNA interference (RNAi)-based therapeutics. This review also discusses the antiviral properties of naturally derived substances, such as quercetin and homoharringtonine, and their mechanisms of action against FMDV. The efficacy of these antiviral agents in inhibiting FMDV replication has been demonstrated by both in vitro and in vivo studies, underscoring their potential as adjunctive tools in FMD control. Despite these advancements, challenges persist, including the emergence of drug-resistant strains, limited in vivo efficacy, and lack of approved antivirals for FMD. This review critically analyzes the advancements in both vaccines and antiviral compounds against FMDV. Continued research is essential to optimize antiviral candidates, address emerging challenges, and improve overall response efforts to FMDV infections.